CAREY, Mark, 2014, Glaciares, cambio climático y desastres naturales. Ciencia y sociedad en el Perú, Lima, IEP e IFEA. 343 pp. - Lossio, Jorge (2015)
Se reseñó el libro: Glaciares, cambio climático y desastres naturales. Ciencia y sociedad en el Perú.